Proceso de atención de enfermería en neonato con hiperbilirrubinemia por incompatibilidad ABO. - Pazos Dávila, Anthony Ricardo (2022)
The purpose of this case study is to present the nursing care process in a neonate with hyperbilirubinemia due to ABO incompatibility in the neonatology area of the Alfredo Novoa Montenegro Hospital in the city of Guaranda. To carry out this case study, a diagnostic methodology was used where the patient's clinical history will be used, together with the physical examination and the medical diagnosis of our patient. Neonatal jaundice is a common finding in newborns where there is a yellow coloration in the eyes, mucous membranes and skin, it also occurs frequently in 60 - 70% of full-term newborns and in a percentage of 80% of infants born prematurely due to elevated serum bilirubin levels in the infant.